ENGINEERING-GEOLOGICAL CONDITIONS OF HOUSE-BUILDING ON A LEFT-BANK OF DNIPER IN KIEV (ON THE EXAMPLE OF TROESCHINA DISTRICT) - HOLUB, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article examines engineering-geological conditions of house-building that exist on a left-bank of Dnipro in Kyiv. The article, which is a result of analysis of engineering-geological researches, summarizes conclusion of geology and hydrogeology of the region, presents methods of engineering-geological researches, and presents engineering-geological elements, which exist in this region. There is conclusion about engineering-geological conditions, about possibilities of an appearance dangerous engineering-geological phenomenon. This article recommends a type of foundation and bases these recommendations.